CD4+ Tumor-infiltrating Lymphocytes in Neoadjuvant Chemotherapy-treated Invasive Breast Cancer of No Special Type - Primariadewi Rustamadji; Elvan Wiyarta; Meike Pramono; Sinta Chaira Maulanisa (Wolters Kluwer Medknow Publications, 2024)
Background: Neoadjuvant chemotherapy (NAC) is an integral component of modern treatment for invasive breast cancer with no special type (IBC-NST). The interaction between the immune system and cancer, particularly through immune-infiltrating lymphocytes (TIL), continues to be studied to understand how treatments like NAC influence the disease progression and response to various therapies. This study was designed to investigate changes in the pattern of CD4+ TIL infiltration before and after NAC. Methods: This retrospective cohort study involved 32 participants. NAC was administered for 3 months, comprising six cycles of chemotherapy. Variables such as age, tumor size, grade, lymphovascular invasion, and regional lymph node metastasis (RLNM) were evaluated. Furthermore, the expression of receptors, estrogen receptor, progesterone receptor, human epidermal growth factor receptor-2 (HER-2), and Ki-67 was evaluated. Infiltration of the tumor by CD4+ TILs was assessed using immunohistochemistry, whereas other data were retrieved from the medical records of the participants. Data were analyzed using R software. Results: There was a significant increase in CD4+ TIL infiltration after NAC administration. Before NAC treatment, there were significant associations between stromal CD4+ TIL with tumor size after NAC (P = 0.047), intratumoral CD4+ TIL with age (P = 0.031), and intratumoral CD4+ TIL with HER-2 status (P = 0.037). After NAC treatment, intratumoral CD4+ TIL was associated with tumor size before NAC (P = 0.009) and RLNM (P = 0.026). Conclusion: NAC is associated with a significant increase in CD4+ TIL infiltration in patients with IBC-NST.